Improving membrane fouling control by maximizing the impact of air bubbles shear in a submerged plate-and-frame membrane module - Eliseus, A. (American Institute of Physics Inc., 2017)
Harvesting microalgae is challenging due to the nature of microalgae having very small size, about similar density to water, and high membrane fouling propensity. Numerous techniques have been implemented for membrane fouling control including periodical cleanings, optimizing operational conditions and imposing shear-rates, such as using air bubbles. Nevertheless, air bubbles effectiveness can still be further improved by maximizing the shear-rates impact to scour foulant on membrane surface. In this paper, a new method to enhance membrane cleaning effect of air bubbles is presented. It was done by tilting the module to maximize contacts of air bubbles on the membrane surface. First of all, we investigate the effect of tilting angle, followed by the effect of switching period, and lastly the effect of aeration rate. The tests were conducted in a lab-scale submerged filtration treating microalgae broth solution. The filtration performance was judged based on steady state permeability. The results showed that increasing tilting lead to further improvement the cleaning efficiency by offering higher permeability. It was also identified that operating at one-sided membrane under optimum tilting angle matches permeability of a two-sided membrane at the same tilting angle, in which the later involved switching mode. Higher aeration rates lead to higher permeability and tilting membrane at 15° can reduce up to 30 of specific aeration demand, and thus improves energy saving. This tilted membrane module can lead to significant cost reduction as well as offers energy saving for membrane fouling control. © 2017 Author(s).